Exploring the application of CHATGPT in plastic surgery: a comprehensive systematic review - Fizzah Arif; Mohammad Khozema Safri; Zenab Shahzad; Sobia Yasmeen; Mohammad Fazlur Rahman; Safdar Ali Shaikh (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the impact of ChatGPT in plasticsurgery research and assess the authenticity of such contributions. Methods: The study conducted a literature search inSep’23 from databases like Pubmed, Google Scholar,SCOPUS, and OVID Medline.The following keywords‘ChatGPT’, ‘chatbot’, ‘reconstruction’, ‘aesthetic’ and‘plastic surgery’ were used. 32 papers were included fromthe initial 131 results of articles. English language articlesfrom November 2022 to July 2023 discussing ChatGPT’srole in plastic and aesthetic surgery were includedwhereas non-English documents, irrelevant content, andnon-academic sources were excluded from the study. Results: The manuscripts included in the systematicreview had a diverse range, including original researcharticles, case reports, letters to the editor, and editorials.Among the included studies, there were 9 originalresearch articles, 1 case report, 23 letters to the editor, and2 editorials. Most publications originated from the UnitedStates (18) and Australia (7). Analysis suggested concerns,such as inaccuracies, plagiarism, outdated knowledge,and lack of personalized advice. Various authorsrecommend using ChatGPT as a supplementary toolrather than a replacement for human decision-making inmedicine. Conclusion: ChatGPT shows potential in plastic surgeryresearch, concerns about inaccuracies and outdatedknowledge may provide deceiving information and italways requires human input and verification.Keywords: Plastic, ChatGPT, Reconstructive Surgery,Aesthetic Surgery, Chatbot. Keywords: Plastic, ChatGPT, Reconstructive Surgery, Aesthetic Surgery, Chatbot.